South Asian cultures of the bomb : atomic publics and the state in India and Pakistan - Abraham, Itty, 1960- (Indiana University Press, 2009)
Since their founding as independent nations, nuclear issues have been key elements of nationalism and the public sphere in both India and Pakistan. Yet the relationship between nuclear arms and civil society in the region is seldom taken into account in conventional security studies. These original and provocative essays examine the political and ideological components of national drives to possess and test nuclear weapons. Equal coverage for comparable issues in each country frames the volume as a genuin.